Economic Preferences Predict COVID-19 Vaccination Intentions and Behavior - Silvia Angerer; Helena Antonie Baier; Daniela Glätzle-Rützler; Philipp Lergetporer; Thomas Rittmannsberger (Institute of Labor Economics (IZA), 2024)
This study investigates the relationship between economic preferences and COVID-19 vaccination readiness using two representative samples of the German population (N > 5,000). We elicited altruism, patience, risk-taking and trust using validated survey questions. We find robust, positive relationships between vaccination readiness and both patience and trust. The positive association between altruism and vaccination readiness vanishes when controlling for the other preference dimensions. No consistent effect emerges for risk-taking. Our results underscore the importance of accounting for the interrelated nature of economic preferences when analyzing their impact on field behavior.
Keywords: C93; D90; I12; 330; economic preferences; vaccination; COVID-19